THE INFLUENCE OF PRODUCT QUALITY AND E-WOM ON PURCHASE DECISIONS FOR SOMETHINC SKINCARE PRODUCTS IN MANADO CITY - Kaliey, Abygaiel; Lapian, S.L.H.V. Joyce; Rogi, Mirah H. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
This study explores the influence of Product Quality and Electronic Word of Mouth (eWOM) on purchase decisions for Somethinc skincare products in Manado City. Product Quality and eWOM are considered as the independent variables, while the dependent variable is Purchase Decision. The research offers valuable insights for skincare businesses to refine product development and enhance digital marketing strategies. A quantitative approach was used, with data gathered from 150 respondents who are Somethinc product users. Data were collected through a questionnaire based on a Likert scale. The analysis includes classical assumption tests, multiple linear regression, and hypothesis testing using the F-test and t-test. The results indicate that both Product Quality and eWOM have a positive influence on consumer purchase decisions for Somethinc skincare products in Manado City.   Keywords: Product Quality, Electronic Word of Mouth (eWOM), Purchase Decision